Cytotoxic, mutagenic and oral pathogen related antimicrobial properties of clinacanthus nutans - Alim, A'attiyyah Ab (2018)
Clinacanthus nutans (C. nutans) locally known as Sabah snake grass is a perennial herb that has been used traditionally in the treatment of various diseases in Malaysia. The objectives of this study were to determine the phytochemical compounds in the ethanol and aqueous extracts of C. nutans leaves using Gas Chromatography Mass Spectrometry (GCMS) and assessing their cytotoxic effect of using MTT assay on human gingival fibroblast cell line and then to evaluate their mutagenic effect using Ames test as well as to determine their antimicrobial properties using agar diffusion test and Minimal Inhibitory Concentration (MIC) assays. A total of 53 phytochemical compounds were identified from the extracts of C. nutans leaves. The compounds were classified into several classes: phenols, flavonoids, terpenoids, fatty acids, alkanes and hydrocarbons, esters, ketones, furans, sulfur and nitrogen compounds. In vitro cytotoxic study of ethanol and aqueous extracts of C. nutans leaves in various concentrations (6,400; 3,200; 1,600; 800; 400; 200; 100; 50 and 25 μg/ml) on human gingival fibroblast cell line (HGF-1) using MTT assay did not exhibit any cytotoxic effect. Ames test on four types of S. Typhimurium strains, TA98, TA100, TA1535 and TA1537 treated with ethanol and aqueous extracts of C. nutans leaves did not show any mutagenic effect both in the presence and absence of metabolic activation system (S9) mix based on the number of revertant colonies. Antimicrobial study using agar well diffusion assay showed that the growth of Staphylococcus aureus (S. aureus) and Actinomyces viscosus (A. viscosus) wereinhibited by the ethanol and aqueous extracts of C. nutans leaves. However, the extracts did not exhibit any antimicrobial activity towards Enterococcus faecalis (E. faecalis), Porhyromonas gingivalis (P. gingivalis) and Candida albicans (C. albicans). Ethanol extract of C. nutans leaves showed better antimicrobial activity compared to the aqueous extract of C. nutans leaves against A. viscosus. Ethanol extract of C. nutans leaves showed MIC value of 102,400 μg/ml against A. viscosus and 204,800 μg/ml against S. aureus. Aqueous extract of C. nutans leaves showed MIC values of 204,800 μg/ml against A. viscosus and S. aureus. The results of the current study show that C. nutans leaves could act as a potential source of antimicrobial agent in combating oral pathogens.